Trabalho decente? para que(m)? um estudo sobre o trabalho de professores contratados na rede estadual de educação paulista - Galdino, Valéria Kemp (2012)
This research seeks to understand issues related to the impacts of education policy geared to teachers hired from the Education Department of the State of São Paulo (SEESP), which was created specifically in Government Serra (2007-2010) and related to the contract teachers. For this we chose the qualitative research whose data were obtained in the statements of teachers who agreeded to participate in a discussion group and analysis of information contained in documents SEESP. Participants in this research teachers hired from the Secretary of Education on the State of São Paulo in a school located in the East the same city. We investigated the extend to which educational policy in São Paulo influences or not the perception that the teacher gives his work. This analysis the author referred in that line to the broader theoretical aspect, the Marxist and some studies aimed at teaching the Paulista State Education Net. We recognize that the late twentieth Century was marked by sweeping changes in the capitalist made of production which had its impacts on State education policy. The analysis of data showed that the perception of being a teacher was changed from primarily Serra Government between 2007-2010 according to scenario of globalization of capital.